2017
DOI: 10.33084/suluh.v3i1.508
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Konseling Kelompok Berbantuan Teknik Problem Solving Untuk Menurunkan Perilaku Membolos Peserta Didik

Abstract: The purpose of this study was to determine the level of truant behaviour in students and find out the effectiveness of group counselling services assisted by problem-solving methods to decrease missing behaviour in students. The research methodology used is the experiment. The population in this study were two palangkaraya public high school students with sample X SMA Negeri 2 palangkaraya. The results showed that group counselling with practical problem-solving techniques to reduce students' truant behaviour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition, to make the group counseling sessions more effective, the researchers also used the problem-solving training technique to help students who were identified as having problems at school, so that they could reduce the problems they faced and understand how to apply problemssolving techniques. Elza (2017) concluded that problem-solving techniques are a way to provide understanding by stimulating students' attention, analyzing and thinking about a problem, and then training their cognitive abilities.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, to make the group counseling sessions more effective, the researchers also used the problem-solving training technique to help students who were identified as having problems at school, so that they could reduce the problems they faced and understand how to apply problemssolving techniques. Elza (2017) concluded that problem-solving techniques are a way to provide understanding by stimulating students' attention, analyzing and thinking about a problem, and then training their cognitive abilities.…”
Section: Introductionmentioning
confidence: 99%